The interior design handbook - Ramstedt, Frida 1979- (Particular Books, 2020)
Introduction -- What makes you feel good? -- Basic principles and rules of thumb -- Bringing it all together -- Colours
First published in Sweden by Roos & Tegnér, 2019
Translated from Swedish
Includes bibliographical references
Keywords: Interior decoration / Handbooks, manuals, etc; Interior architecture / Handbooks, manuals, etc; Interior architecture; Interior decoration; Handbooks and manuals